PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN DENGAN ACCURATE - Novie Astuti Setianingsih; Atik Tri Andari; Wiwiek Kusumaningasmoro; Eti Putranti; Elmi Rakhma Aalin (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2020)
The purpose of this community service is to make financial reports for UMKM players in Kalirong Village, Tarokan District using accurate online applications. Implementation of these community activities using cycle learning, namely: 1. Exploration (description) that is, this exploration method means to dig up the knowledge about the preparation of financial statements; 2. Explanation (empirical) namely this explanatory method is to introduce how the concept and how to use accurate applications; 3. Application (aductive), namely this method is to apply it to the preparation of financial statements accurately in their respective companies. This online financial report preparation training activity for UMKM in Kalirong Village, Tarokan District was held on September 21-26, 2020.